Development, Validation, and Results of a Survey of Personal Electronic Device Use Among 299 Anesthesia Providers From a Single Institution. (17th August 2021) - Porter, Steven B.; Renew, J. Ross; Paredes, Stephania; Roscher, Christopher R.; Plevak, Matthew F.; Yost, Kathleen J.
Abstract : BACKGROUND: The pattern of perioperative use of personal electronic devices (PEDs) among anesthesia providers in the United States is unknown. METHODS: We developed a 31-question anonymous survey of perioperative PED use that was sent to 813 anesthesiologists, anesthesiology residents, and certified registered nurse anesthetists at 3 sites within one health system. The electronic survey assessed patterns of PED use inside the operating room (OR), outside the OR, and observed in others. Questions were designed to explore the various purposes for PED use, the potential impact of specific hospital policies or awareness of medicolegal risk on PED use, and whether PED was a source of perioperative distraction. RESULTS: The overall survey response rate was 36.8% (n = 299). With regard to often/frequent PED activity inside the OR, 24% reported texting, 5% reported talking on the phone, and 11% reported browsing on the Internet. With regard to often/frequent PED activity outside the OR, 88% reported texting, 26% reported talking on the phone, and 63% reported browsing the Internet. With regard to often/frequent PED activity observed in others, 52% reported others texting, 14% reported others talking on the phone, and 34% reported others browsing the Internet. Two percent of respondents self-reported a distraction compared to 15% who had observed a distraction in others. Eighty percent of respondents recognized PED as a potential distraction for patient safety. CONCLUSIONS: Our data reinforce that PED use is prevalent among anesthesia providers.